Industrial-Scale Preparation of a Key Intermediate for the Manufacture of Therapeutic SGLT2 Inhibitors - Huang, Lei; Zhang, Yi; Shan, Xiao-Hui; Liu, Yu; Li, Jian-Qi (Pharmaceutical Fronts, 2022)
(3R,4S,5R,6R)-3,4,5-tris(benzyloxy)-6-methyltetrahydro-2H-pyran-2-one (1) is a key intermediate for the preparation of promising SGLT2 inhibitors currently undergoing clinical tests for diabetes therapy. However, fewer reports have demonstrated the preparation of compound 1 at an industrial scale. In this article, an efficient preparation of the intermediate for the industrial production was explored from commercially available methyl-α-D-glucopyranoside in seven steps, including TBS protection, benzyl protection, TBS removal, iodination, reduction, demethylation, and oxidation. The batch of the validation process was 42.82 kg with a HPLC purity of 99.31%. The main advantages of this approach are that the total cost is lower than the reported laboratory-scale synthetic method, the quality is reproducible, and the process is safe and environmentally friendly.
Keywords: SGLT2 inhibitors; (3R,4S,5R,6R)-3,4,5-tris(benzyloxy)-6-methyltetrahydro-2H-pyran-2-one; industrial production; safe and environmentally friendly